Răspuns :
Răspuns:
Explicație pas cu pas:
[tex]\displaystyle 0,5-\frac{1}{2} \times(\frac{3}{4} -0,25)=\frac{5}{10}^{(5} -\frac{1}{2} \times (\frac{3}{4} -\frac{25}{100} ^{(25})=\frac{1}{5} -\frac{1}{2} \times(\frac{3}{4} -\frac{1}{4} )=\frac{1}{5} -\frac{1}{\not2} \times \frac{\not2}{4} =^{(4}\frac{1}{5}-^{(5}\frac{1}{4} = \frac{4}{20} -\frac{5}{20} =-\frac{1}{20} =-0,05[/tex]
[tex]\displaystyle 0,75-0,17\times(\frac{19}{10} -1,5)=0,75-0,17\times (1,9 - 1,5)=0,75-0,17\times 1,4=0,75- 0,238=0,512[/tex]
[tex]\displaystyle (\frac{1}{3} +0,25)\times(1+\frac{5}{7} )=(\frac{1}{3} +\frac{25}{100} ^{(25})\times(\frac{7}{7} +\frac{5}{7} )=(^{(4}\frac{1}{3} +^{(3}\frac{1}{4} )\times \frac{12}{7} =(\frac{4}{12} +\frac{3}{12} )\times \frac{\12}{7} =\frac{7}{\not12} \times\frac{\not12}{7} =1[/tex]
[tex]\displaystyle 0,a=\frac{a}{10} \\ 0,ab=\frac{ab}{100} \\\frac{ab}{10} =a,b[/tex]